Constant Switching Frequency and Torque Ripple Minimization of DTC of Induction Motor Drives with Three-level NPC Inverter - Huzainirah Ismail; Fazlli Patkar; Auzani Jidin; Aiman Zakwan Jidin; Noor Azida Noor Azlan; Tole Sutikno (Institute of Advanced Engineering and Science, 2017)
Direct Torque Control (DTC) is widely applied for ac motor drives as it offers high performance torque control with a simple control strategy. However, conventional DTC poses some disadvantages especially in term of variable switching frequency and large torque ripple due to the utilization of torque hysteresis controller. Other than that, performance of conventional DTC fed by two-level inverter is also restricted by the limited numbers of voltage vectors which lead to inappropriate selection of voltage vectors for different speed operations. This research aims to propose a Constant Switching Frequency (CSF) torque controller for DTC of induction motor (IM) fed by three-level Neutral-Point Clamped (NPC) inverter. The proposed torque controller utilizes PI controller which apply different gain for different speed operation. Besides, the utilization of NPC inverter provides greater number of voltage vectors which allow appropriate selection of voltage vectors for different operating condition. Using the proposed method, the improvement of DTC drives in term of producing a constant switching operation and minimizing torque ripple are achieved and validated via experimental results.